Rhombencephalitis due to Listeria Monocytogenes Infection in the Immunocompetent Patient: A Case Report - Fettah Eren (Van Tip Dergisi, 2019)
Listeria monocytogenes is a gram positive microorganism that can cause multiorgan involvement. If brainstem involvement due to this microorganism occurs, it is called rhombencephalitis. There are nonspecific prodromal symptoms at the begining. Progressive brainstem symptoms and seizures can be added. 27 year old male patient presented with dizziness and ataxia for 15 days. It was learned that he had traveled to Saudi Arabia 2 months ago. Restricted abduction of left eye, left facial hemihypoesthesia, ataxia, dysmetria and bilateral Babinski sign positive were detected. In brain imaging, hyperintensity was detected at T2, DWI and FLAIR sequences in mesencephalon, pons and bulbus localization. Listeria monocytogenes in blood culture was detected. Immune deficit was not detected. Intravenous 150 mg/kg/day ampicillin was started. On the 12th day of admission, the patient died associated with respiratory deficit. Listeria monocytogenes should be considered in patients with resistant of classical antibiotic treatment cases who present with atypical brainstem symptoms. Typical brainstem involvement on brain imaging can be useful for diagnosis. Early recognition and treatment is the most important prognostic factor.